PERLINDUNGAN TERHADAP KORBAN KEJAHATAN EKONOMI DI BIDANG PERBANKAN - Apriliana Puspitasari, Rachmawati; Satyayudha Dananjaya, Nyoman (Kertha Wicara : Journal Ilmu Hukum, 2014)
Economic crimes in the banking sector can be said to be a white collar crime because the crime committed by the offender by way of abusing the trust given to him from the public.Therefore, white collar crime often occurs in organizations where people put trust in that bank. The impact of the abuse of the trust that is the emergence of a victim of economic crime in the banking field. For it is necessary to study the steps or policies that need to be taken in order to protect the victims of economic crime in banking because when viewed from the existing regulations there are still the norm vacancy. This paper aims to determine the protection of victims of economic crime in the banking sector. Given the losses large enough, then the protection of the victim (bank customers ) it was time to do. Then it takes the concept of protection of victims of economic crime in the banking sector by using the criminal law.
Keywords: Protection,Victim, Economy Crime, Banking